Goodnight moon buenas noches, luna : 123 : a counting book : un libro para contar - Brown, Margaret Wise, 1910-1952; Hurd, Clement, 1908-1988 (New York : Rayo, 2007)
A little bunny counts and bids goodnight to all the objects in his room before falling asleep.
Newborn-5.
Keywords: Bedtime -- Juvenile fiction; Rabbits -- Juvenile fiction; Counting -- Juvenile literature; Hora de acostarse -- Novela juvenil; Conejos -- Novela juvenil; Contar (Enumerar) -- Literatura juvenil